Upaya Membangun Strategic Marketing Outcomes Berbasis Pada Relationship Marketing Dan Power - Alimuddin Rizal Riva’i (Universitas Airlangga, 2010)
This study is developed by proposing a grand theoretical model and empirical models: The impact of Coercive Power in Relationship Marketing and Strategic Marketing Outcomes based on Relationship Marketing Theory and Power-Dependence Theory. Spesifically, to investigates the issue of power in business-to-business relationships and the impacts of coercive power to the key variables in the Commitment-Trust Theory (Trust, Relationship Commitment, Cooperation); to integrate Relationship Outcomes variables (loyalty, strong relationship, positive word of mouth) as a value of lifetime relationships, and to builds the strategic marketing outcomes (cooperation synergy, competitive positional advantages, marketing performance). This study was conducted by proposing three empirical models and was tested successfully on Indonesia tourism industry. There are 190 respondents as managers of tourism organization. The data was tested using several statistical tools such as SPSS and Structural Equation Modeling (SEM). The finding of this research are as follows :(1) Coercive Power has no significant association between trust, and positive-significant between relationship commitment and cooperation; 2) This study shows that the coercive power does not destroye a relationship but has a capability to control the interaction process; (3) This suggests that there are other variables of driving relationships besides the trust-commitment-based relationships suggested by Morgan dan Hunt (1994). There are both trust-based and power-based relationships.However, coercive power it self is not found to be driver of relationship outcomes. The Suggested coercive power and trust are the relationship bases of relationship marketing; (4) Value of Lifetime Relationships (Loyalty, Strong Relationship, Positive “WoM”) as a relationship outcomes, and important variables cause to grow up cooperation synergy. This is one spesific research finding.; (5) and the last, The Cooperation Synergy as an important variable will in crease the competitive positional advantages and marketing performance. The result of the study is important to develop and maintain relationship with stakeholders (partners, competitors, complementary organization) in tourism industry which based on market-based views and resources-based views. This integrated approach can achieve greater outcomes in relationship marketing of business-to-business relationship activities. In tourism policy, it is important to formulate “The Grand Tourism Strategy Based on Local Resources and Cultures”.